PENGARUH PENGUKUSAN PADA EMPAT JENIS KAYU KERING UDARA TERHADAP IMPREGNASI DENGAN BAHAN PENGAWET CCA - Barly Barly; Pipin Permadi (Jurnal Penelitian Hasil Hutan, 1989)
Impregnation    under  pressure  is  the  most  effective  way  of  applying  preservative   to  timbers,   but  not  all species can be treated  effectively  using  the  method.   Air-dried  timbers  of  5 cm  x  5 cm x  100 cm in dimension   were impregnated   with preservative   used  for  constructional   purposes.   Part of  wood  samples  was presteamed.   Prior to  the preservative   treatment both  groups  were reconditioned    to  the same  moisture  content   as the  reference   material  (air dried).Retention  and  penetration   figures  have  increased as presteaming   was applied.   The  result revealed  that  two  timbers preserved   met   the  standard   requirement.    The  preservation   schedule  proposed   for  the  timbers  is presented   in this paper.